Determination of influencing metricsin water fall model - David, K; Anand, R (International Journal of Engineering and Technology, 2018)
You cannot control what you canâ€™t measure - Tom DeMarco -Metrics plays a critical role in any industry. The metrics can tell the senior management the health of the activity in that organization. In the paper, we have studied the relationship between the metrics and the quality of deliverables. Once the right metrics are identified for a particular phasein the life cycle model it will help the project manager to proactive-ly detect the issues earlier and arrest the defects. This can help the project teams to deliver the product on time without defects. There by the cost of the projects can be reduced which in turn will have high customer satisfaction.Â Â